Orphanages without orphans? Reflections of moral anthropology on orphanages for Indian children (2019)
In the first decades of the twentieth century, a group of Spanish Capuchin missionaries built a series of educational institutions in northern Colombia that they called “orphanages” (although most of the children educated there were not orphans) and that represented the implementation of a new “conversion”/ “civilization” strategy for the region’s Indian groups after several decades of failure. This article proposes to analyse the process that led the missionaries to theorize this practice of separating children from their families as the most relevant to their evangelization work. How has this method – now considered one of the most controversial from an ethical-moral point of view – been gradually built as the best solution to convert the indigenous populations of northern Colombia and incorporate them into the nation? And above all, what are the argumentative records that the missionaries used to convince the public authorities to support this enterprise based on the abduction of indigenous children from their families? © koninklijke brill nv, leiden, 2019